The Financial Accelerator: Evidence using a procedure of Structural Model Design - Roger Hammersland; Dag Henning Jacobsen (Statistics Norway, Research Department, 2008)
We find empirical evidence of a financial accelerator using a data based procedure of Structural Model Design. Credit to firms, asset prices and aggregate economic activity interact over the business cycle in our empirical model of a dynamic economy. Furthermore, the interdependence between credit and asset prices creates a mechanism by which the effects of shocks persist and amplify. However, while innovations to asset prices and credit do cause short-run movements in production, and while real activity spurs credit, such innovations do not precede real economy movements in the long run. Hence, there obviously is a case for Modigliani-Miller in the long run.
Keywords: C30; C32; C50; C51; C53; E44; E51; 330; Financial variables and the real economy; The Financial Accelerator; Business fluctuations; Structural vector Error Correction modeling; Identification; Cointegration.